2018
DOI: 10.1002/per.2171
|View full text |Cite
|
Sign up to set email alerts
|

Same Same, but Different? Relations between Facets of Conscientiousness and Grit

Abstract: The constructs grit and conscientiousness are closely connected. However, this relationship has not been analysed while accounting for the complex structure of conscientiousness and the multifaceted conception of grit (perseverance of effort; consistency of interest). In this study, we analysed the connection while considering the hierarchical structure of conscientiousness, differentiating between a superordinate factor, a first‐level common factor (industriousness), and lower level unique factors. Drawing on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
108
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 35 publications
8
108
2
3
Order By: Relevance
“…This aligns with what has been found in the larger body of literature on grit, suggesting that grit might be similar to facets of conscientiousness that include self-discipline and achievement striving (e.g. Credé, Tynan, and Harms 2016;Rimfeld et al 2016;Schmidt et al 2018). Eskreis-Winkler et al (2014) have not denied this relationship, but have emphasised that grit differs from facets of conscientiousness by its 'extreme stamina in terms of particular interests and applied effort towards these interests' (2).…”
Section: Inconsistent Conceptualisations Of Gritsupporting
confidence: 69%
“…This aligns with what has been found in the larger body of literature on grit, suggesting that grit might be similar to facets of conscientiousness that include self-discipline and achievement striving (e.g. Credé, Tynan, and Harms 2016;Rimfeld et al 2016;Schmidt et al 2018). Eskreis-Winkler et al (2014) have not denied this relationship, but have emphasised that grit differs from facets of conscientiousness by its 'extreme stamina in terms of particular interests and applied effort towards these interests' (2).…”
Section: Inconsistent Conceptualisations Of Gritsupporting
confidence: 69%
“…Grit shows particularly close definitional overlap with the Industriousness (or Productiveness) facet of Conscientiousness, as in-depth studies on the composition of Conscientiousness have shown [19,20]. The same is true for some of the facets of commonly used comprehensive measures to assess Conscientiousness, such as the Achievement-striving and Self-discipline facets of Conscientiousness in the Revised NEO Personality Inventory (NEO-PI-R [21]; for a discussion see [8]), as well as the Productiveness and Responsibility facets of the Big Five Inventory-2 (BFI-2 [15]), which we use in the present investigation. Given the close relationships between Grit and particularly those facets of Conscientiousness that focus on proactivity and persistence, a view that has been espoused by several authors is that Grit should best be conceived of as facet of Conscientiousness, rather than as a measure for the broader Conscientiousness domain (e.g., [22]).…”
Section: Conceptual and Empirical Distinctions Between Grit And Conscmentioning
confidence: 99%
“…Even though the view that Grit represents a construct within-or a facet of-the Conscientiousness domain is an emerging consensus to which we subscribe in the present investigation, few studies have actually investigated the relationships between facets of Grit and facets of Conscientiousness (as opposed to domain-level measures of Conscientiousness) empirically. Apart from the study by Abuhassàn and Bates [18] named earlier, a recent study by Schmidt et al [8] used a more comprehensive and broader measure with a focus on the industriousness aspects of Conscientiousness, the NEO-PI-R [21]. The study showed that Grit shared nearly 90% of its variance with Conscientiousness on the latent-variable level.…”
Section: Conceptual and Empirical Distinctions Between Grit And Conscmentioning
confidence: 99%
See 1 more Smart Citation
“…Grit, as a personality trait, is interpreted as trait-level perseverance with a passion for long-term goals, and it has been shown to predict an individual's achievement in challenging domains over and beyond measures of talent (Duckworth et al, 2007;. According to Duckworth et al (2007), although there has been some empirical evidence for a close relationship between grit and conscientiousness (e.g., Ivcevic and Brackett, 2014;Rimfeld et al, 2016;Schmidt et al, 2018), grit distinguishes from the traditionally measured facets of Big Five Conscientiousness in its focusing on stamina. More specifically, grit shows that one is available to keep effort and interest in projects that may take months or even more to accomplish.…”
Section: Introductionmentioning
confidence: 99%